The dimensions of job satisfaction among expatriates in Malaysia / Wan Nur Hatira Wan Amri and Aimi Najah Miskon - Wan Amri, Wan Nur Hatira; Miskon, Aimi Najah (2013)
Job satisfaction becomes a common issue faced by expatriate in many organizations in Malaysia today. In almost all cases, the responsibilities of expatriates in host country will be different than they are used to overseeing. It affects expatriate mental and physical health and in the long run it could affect the organization performance. This research study on four dimensions that influence Job Satisfaction among the expatriates in Malaysia which are Job Characteristics, Salary, Co-workers and Career Prospects. The expatriates in Malaysia which come from ages range from 25 to 46 years old and from different nationality which consists of Asia, Africa, Europe and Middle Eastern. Data is collected through questionnaire distributed to 50 expatriates in Malaysia using non probability sampling. Result of the present study showed that the significant correlation relationship between factors that influence job satisfaction and job satisfaction. This study also used regression backward analysis in order to identify which factors is most significant to job satisfaction among expatriates in Malaysia. This study is said to be beneficial to the companies in Malaysia especially if they are facing low job satisfaction among expatriates. It will help them to gain awareness on the main factor and help them to manage the issue from getting worse. Recommendations for future research are also having been discussed.